1991
DOI: 10.1073/pnas.88.12.5302
|View full text |Cite
|
Sign up to set email alerts
|

A protein geranylgeranyltransferase from bovine brain: implications for protein prenylation specificity.

Abstract: A protein geranylgeranyltransferase (PGT) that catalyzes the transfer of a 20-carbon prenyl group from geranylgeranyl pyrophosphate to a cysteine residue in protein and peptide acceptors was detected in bovine brain cytosol and partially purified. The enzyme was shown to be distinct from a previously characterized protein farnesyltransferase (PFT). The PGT selectively geranylgeranylated a synthetic peptide corresponding to the C terminus of the y6 subunit of bovine brain G proteins, which have previously been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
197
0
2

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(204 citation statements)
references
References 35 publications
5
197
0
2
Order By: Relevance
“…As shown in Figure 9( [2,18]; (ii) DPR1 protein purified from E. coli can reconstitute FTase when added to the extracts prepared from dprl mutant cells [18]; (iii) sequences of DPR1 and RAM2 proteins share a low, but significant, similarity with ,-and a-subunits respectively of the mammalian FTase [19,20]; (iv) extracts of E. coli cells expressing both DPRI and RAM2 exhibit FTase activity [21]. What has been lacking in these studies is the direct demonstration of [10] reported similar findings using the mammalian FTase and peptide substrates. Thus changing the C-terminal amino acid of an FTase substrate to leucine alters the substrate to be preferentially utilized by GGTase, but does not exclude it being used as an FTase substrate.…”
Section: Peptide Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 9( [2,18]; (ii) DPR1 protein purified from E. coli can reconstitute FTase when added to the extracts prepared from dprl mutant cells [18]; (iii) sequences of DPR1 and RAM2 proteins share a low, but significant, similarity with ,-and a-subunits respectively of the mammalian FTase [19,20]; (iv) extracts of E. coli cells expressing both DPRI and RAM2 exhibit FTase activity [21]. What has been lacking in these studies is the direct demonstration of [10] reported similar findings using the mammalian FTase and peptide substrates. Thus changing the C-terminal amino acid of an FTase substrate to leucine alters the substrate to be preferentially utilized by GGTase, but does not exclude it being used as an FTase substrate.…”
Section: Peptide Inhibitionmentioning
confidence: 99%
“…identity between DPR1 and the f-subunit of the mammalian Another type of protein prenylation involves the addition of a FTase as well as between RAM2 and the a-subunit of the geranylgeranyl group, and protein geranylgeranyltransferases mammalian FTase [19,20]. In addition, FTase activity was (GGTases) are responsible for this type of modification [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and biochemical studies on protein prenylation have revealed three distinct enzymes, each consisting of evolutionarily conserved subunits (Chen et al, 1991b;Kohl et al, 1991). Geranylgeranyl transferase I (GGTase I or CAAX GGTase) Seabra et al, 1991;Yokoyama et al, 1991;Moomaw and Casey, 1992) and farnesyl transferase (FTase) (Reiss et al, 1990(Reiss et al, , 1991aChen et al, 1991a;Seabra et al, 1991) modify proteins containing the Cys-Ali-Ali-X sequence Yokoyama et al, 1991;Reiss et al, 1991b;Kinsella et al, 1991), form heterodimers, and share a common a subunit (Seabra et al, 1991). The third prenyltransferase, named GGTase II or Rab GGTase (Seabra et al, 1992), modifies proteins that terminate with GGCC or CXC and consists of three nonidentical subunits (Seabra et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro study of substrate specificity using partially purified FTase and GGTase I is basically consistent with this rule. However, the FTase can modify proteins with C-terminal leucine to a limited extent when a high concentration of the protein substrate is used (Yokoyama et al, 1991). This in vitro cross-specificity may be explained by the fact that the two enzymes not only share a common a subunit but have :3 subunits that, though not identical, are nevertheless similar to each other.…”
Section: Introductionmentioning
confidence: 99%
“…These modifications include derivitization of the cysteine sulfhydryl with an isoprenoid moiety followed by the endoproteolytic removal of the -AAX tripeptide and methylation of the cysteine ␣-carboxyl group. When the X amino acid is S, C, Q, or M, a 15-carbon farnesyl residue is attached in thioether linkage to the cysteine (3), whereas when X is a leucine, a 20-carbon geranylgeranyl residue is found instead (4).…”
mentioning
confidence: 99%